Analisis Pengaruh Efisiensi Besaran Ruang terhadap Penggunaan Material Kayu (Studi Kasus Microlibrary Warak Kayu) - Ilham Dwi Saputra; Aldy Laudy; Angga Ardiansyah (GLOBAL SCIENTS PUBLISHER, 2026)
Space efficiency is an important aspect in the design of library buildings because it is directly related to the optimization of spatial functions and the economic value of the building. As a public facility, a library has diverse spatial requirements; therefore, efficient spatial management is necessary to optimally accommodate user activities. In addition, the use of wood materials as architectural elements provides flexibility in spatial arrangement and offers potential efficiency in construction processes. This study aims to analyze the influence of space efficiency on the economic value of wooden library buildings through a case study of Microlibrary Warak Kayu designed by SHAU Indonesia. The research employs a case study method with a descriptive-analytical approach. The analysis was conducted by identifying spatial configurations, calculating space efficiency based on the ratio of effective area to the total building area, and examining its implications for user capacity and the conceptual economic value of the building. The results indicate that efficient spatial planning can increase space utilization capacity and maximize productive areas, thereby contributing to the enhancement of the building’s economic value. Furthermore, the use of wood materials supports spatial flexibility, allowing spaces to be utilized more optimally.